Identification of a Ribosomal Protein RpsB as a Surface-Exposed Protein and Adhesin of Rickettsia heilongjiangensis. (9th July 2019) - Qi, Yong; Rao, Jixian; Shen, Wanpeng; Li, Jiameng; Zeng, Wenwen; Zheng, Shulong; Liu, Suyun; Li, Yuping; Wang, Bijun; Wu, Fan; Li, Yuchao; Li, Yuexi
Abstract : Rickettsia heilongjiangensis is an obligate intracellular bacterium that is responsible for far-eastern spotted fever. Surface-exposed proteins (SEPs) play important roles in its pathogenesis. Previous work identified a ribosomal protein RpsB as an SEP by biotin-avidin affinity, a seroreactive antigen, and a diagnostic candidate protein, indicating that it might play an important role in the pathogenesis of rickettsiae. However, in the absence of other evidence, its subcellular location of being surface-exposed was puzzling because ribosomal proteins are located in the cytoplasm. In the present study, the subcellular location of RpsB was analyzed with bioinformatics tools coupled with immunoelectron microscopy. The adhesion ability of RpsB was evaluated by protein microarray and cellular ELISA. Consequently, different bioinformatics tools gave different location predication results. Thus, RpsB was found in the cytoplasma and inner and outer membranes of R. heilongjiangensis by transmission electron microscopy. Protein microarray and cellular ELISA showed that RpsB binds to the host cell surface and its adhesion ability was even stronger than the known adhesin Adr1. In conclusion, RpsB was visually and directly shown for the time to be an SEP of rickettsiae and might be an important ligand and adhesin of rickettsiae. Its roles in pathogenesis warrant further study.